'Death Solves All Problems': The Authoritarian Model of Counterinsurgency. Issue 1 (2nd January 2016) - Byman, Daniel
ABSTRACT: Authoritarian states are often surprisingly successful counterinsurgents. In particular, authoritarians often repress on a vast scale and inhibit insurgent organization, transfer populations, have excellent intelligence penetration, and can counter war weariness in ways not available to democracies. Authoritarians, however, come to counterinsurgency with many disadvantages. They cannot rely on many of their conscripts. Corruption creates numerous problems, and authoritarian system often inhibits learning. Similarly, the politicized command structure often produces poor officers and discourages initiative. The repression they use often makes future unrest more likely. Finally, authoritarian regimes may find it harder to cut peace deals and win over pro-insurgent populations.